2009
DOI: 10.1093/treephys/tpp088
|View full text |Cite
|
Sign up to set email alerts
|

Pinus pinaster seedlings and their fungal symbionts show high plasticity in phosphorus acquisition in acidic soils

Abstract: Young seedlings of maritime pine (Pinus pinaster Soland in Aït.) were grown in rhizoboxes using intact spodosol soil samples from the southwest of France, in Landes of Gascogne, presenting a large variation of phosphorus (P) availability. Soils were collected from a 93-year-old unfertilized stand and a 13-year-old P. pinaster stand with regular annual fertilization of either only P or P and nitrogen (N). After 6 months of culture in controlled conditions, different morphotypes of ectomycorrhiza (ECM) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Higher values of surface-bound ACP have also been measured in ectomycorrhizal roots (see, e.g. Ali et al 2009; van Aarle and Plassard 2010) and hyphae (van Aarle and Plassard 2010) belonging to ectomycorrhizal plants grown in soil with a low level of available P, confirming the results obtained in vitro. In contrast, it seems that the presence of organic P did not activate the production of ACP in ECM fungi as no differences in enzyme production were found after growth on inorganic and organic P sources (Antibus et al 1992;Nygren and Rosling 2009).…”
Section: Introductionsupporting
confidence: 78%
“…Higher values of surface-bound ACP have also been measured in ectomycorrhizal roots (see, e.g. Ali et al 2009; van Aarle and Plassard 2010) and hyphae (van Aarle and Plassard 2010) belonging to ectomycorrhizal plants grown in soil with a low level of available P, confirming the results obtained in vitro. In contrast, it seems that the presence of organic P did not activate the production of ACP in ECM fungi as no differences in enzyme production were found after growth on inorganic and organic P sources (Antibus et al 1992;Nygren and Rosling 2009).…”
Section: Introductionsupporting
confidence: 78%
“…Utilizing stable P forms requires energy associated with the release of organic acids or phosphatases for solubilizing recalcitrant inorganic or organic P forms (Cairney, ). Ali, Louche, Legname, Duchemin, and Plassard () observed that P uptake by mycorrhizal fungi is not sufficient to fulfil the P requirement of the host when P inorg‐avail levels are too low. Our results suggest that P resorption represents a cost‐effective strategy to cope with P deficiency when the P inorg‐avail content in the soil is low.…”
Section: Discussionmentioning
confidence: 99%
“…Xylanase is produced and released mostly by fungi in the forest environment [46]. Ali et al [47] showed that in coniferous tree species such as Pinus taeda L., ectomycorrhizal fungi produce extracellular phosphatase to improve phosphorus uptake. In our study, the mature forest soil had higher fungal biomass than other soils and provided more xylanase and phosphatase (Table 3).…”
Section: Discussionmentioning
confidence: 99%